Software Development of Food Combining Guidelines Using Smartphone-Based On Android In Bandung - Widianto, Mochammad Haldi (Universitas Pendidikan Indonesia (UPI), 2023)
The number of applications circulating, some researchers do not want to be left behind, one of which is a food-based application that can be used as an Android mobile-based food combination guide. Examples of food applications that are used to overcome the problem of vitamins, minerals and energy needed by the body. Basically, food applications are needed to help citizens by determining the food consolidation menu. Providing information in the form of how much health content and plans will be carried out, this aims to provide information. To get recipe suggestions, clients are initially required to select a photo image from the camera. After the application will send image suggestions to clarify and get the label name of the ingredients, by getting a signal to the system to send the ingredients to the nutritionist to collect the ingredients. Once developed, the framework shows the side effects of labeling and collecting ingredients in the application. Once an ingredient is selected, the system sends the component name to Food2Fork to get the recipe. The recipe will be displayed before being displayed to the system. The test results can be ascertained that the Android application can work well.